Required strength estimation of a cemented backfill with the front wall exposed and back wall pressured. (2018) - Liu, Guangsheng; Li, Li; Yang, Xiaocong; Guo, Lijie
Determining the required strength is a critical task in backfilled stopes design. Over the years, several solutions have been proposed by considering a backfill with one face exposed and confined by three rock walls. In practice, a cemented backfill may be in contact with an uncemented backfill and exposed on the opposite side. The uncemented backfill can apply a pressure on the exposed cemented backfill and affects its stability. In this study, a lateral pressure equal to the isostatic overburden pressure is considered for the uncemented backfill. An analytical solution is proposed to evaluate the minimum required strength of the cemented backfill exposed on one side, pressured by the uncemented backfill on the opposite side, and confined by two rock walls. The proposed analytical solution is validated by numerical simulations with FLAC 3D .